UPAYA GURU PEMBIMBING DALAM MENGEMBANGKAN POTENSI PSIKIS PESERTA DIDIK DI SMP NEGERI 9 PADANG - Yunas, Rini Septiani; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problem  this  research  is how  would be  effort  a directship and teacher in developing  psychology potency  the pupil  at   Junior High School  Negeri  9  Padang.  These research  its purpose  about  is  description   (1)  Be effort  a teacher  and directship   in developing  intellectual  and inteligency  potency the  pupil. (2)  Be effort  a teacher and directship  in developing  emotional and  inteligency  the pupil . This  research form  is descriptive research .The population   these   research  are  all of the pupil at  Junior High School Negeri  9   by sum of  718 person and  88 sampling  person .These research  being usefullProportionate  Stratified  Random Samplingor stratified  sampling   that is  get  off the sample from the populationhave  divided in stratified   or  strata . The resources data  whole is mean in the research  have  offered     initial    from  proving  its data. These  tool and equipment  all of  group data  are usefull  a questioner sheet. The  data is examined  by usefullpercently technic. Concomitan  here  research  and resulting  have been found  like is  footnote below .  (1)  Be effort  directship and teacher  in developing   intellectual  the pupil   at  Junior High School  Negeri 9 Padang   have proved  into  good  category. (2) Be effort  directship and teacher    in developing    emotional  inteligency  the  pupil   at  Junior High School Negeri 9 Padang  into good category. Base on    find out this  research  to recommendation   on : directship and teacher  proved  to improvement  psycho potency   all of the  pupil  at  Junior High School  Negeri   9  Padang  with optimally.